Management of Airway Clearance is Ineffective in Patients with Tuberculosis & Mediastinal Tumors - Rizki, Indrianti Alvini; Nugraha, Bambang Aditya; Platini, Hesti (Universitas Negeri Gorontalo, 2024)
Ineffective airway clearance is a common problem in pulmonary tuberculosis patients. This condition occurs due to an infectious process that causes an inflammatory response and excessive secretion production. The mediastinal tumor experienced by the patient resulted in the patient's condition getting worse because the lump in the mediastinal area pressed on the airway so that phlegm/secretions were difficult to expel. This study aimed to describe the ineffective management of airway clearance in patients with pulmonary tuberculosis, pleural effusion, and mediastinal tumors. This study uses a descriptive observational research design in the form of a case report using a nursing care approach. The subject of this study was a 34 year old woman with a medical diagnosis of pulmonary tuberculosis, pleural effusion, and mediastinal tumor. The intervention carried out, namely managing airway clearance, was not effective. Some of the actions carried out include semi-fowler position, collaborative administration of 3 lpm oxygen, combivent and pulmicort nebulization 3 times/day, and suctioning. After carrying out nursing procedures for 3 x 24 hours, the patient said he felt more comfortable in the semi-Fowler's position, she felt the shortness of breath was reduced after nebulization but the shortness of breath became worse again sometime later, the patient said he had difficulty expelling phlegm so his shortness of breath did not improve, SaO2 100%, RR 18 times/minute, and wheezing (-). It can be concluded that the interventions can reduce symptoms but cannot solve the problem. Management of ineffective airway clearance in this case cannot be done independently by the nurse. Collaboration is needed by considering the need for surgery and pharmacological therapy.